Assessment of Livelihood Resilience during the COVID-19 Pandemic among Smallholder Households in Pasirtalaga Village, Karawang, Indonesia - Sulandjari, Kuswarini; Azzahra, Fatimah (KnE Social Sciences, 2024)
The COVID-19 pandemic as a global crisis affected the many lives in Indonesia and the farming community of Pasirtalaga Village. The primary source of livelihood in this village is agriculture and several households depend on the income of family members who have migrated. Although the direct effects of pandemic are not evident, significant changes have been observed in the daily lives of the community residents, as indicated by the loss of shipments due to layoffs of family members. The government policies imposing restrictions on community activities have also caused a decline in the economy. Based on these conditions, farmer households depend on their livelihood assets as a buffer capacity to achieve a level of resilience. Therefore, this study aimed to analyze the relationship between the five capital assets and household livelihood resilience of farmers in Pasirtalaga Village, Telagasari, Karawang. The study was carried out using a quantitative method supported by qualitative data. The results showed a directly proportional relationship between the level of ownership of living capital and households livelihood resilience of farmers in Pasirtalaga Village. This indicated that a higher ownership of living capital led to a greater level of resilience in facing the crisis due to the COVID-19 pandemic. Keywords: COVID-19 pandemic, livelihood resilience, smallholder households